Correlations between agronomic traits in papaya tree (Carica papaya L.) grown under subtropical climate of Brazil - Silva, Marcelo de Souza [UNESP]; Leonel, Sarita [UNESP]; Souza, Jackson Mirellys Azevêdo [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Bolfarini, Ana Carolina Batista [UNESP]; Júnior, Marcelo Almeida de Oliveira [UNESP] (Southern Cross Publishing, 2018)
The current study aimed at evaluating the correlations between agronomic traits in papaya trees grown under Brazilian subtropical climate. A randomized block design with three treatments (Sunrise Solo, Tainung no 1 and Local variety) was used. The experiment was laid out in seven blocks and five plants per plot. The following traits were assessed: plant height; insertion height of the first fruits; stem diameter; male, female, and hermaphrodite plants percentage; fruit number per plant; production; yield; percentage of normal fruits; carpelloid and pentandric fruits percentage; internal cavity diameter; fruit matter; pulp and seed yield; seeds number; soluble solids; titratable acidity; ratio and technological index. Results indicated that seed performance can be used as indirect selection criteria for genetic improvement of Sunrise Solo seeds (correlation between SP and FNP, PRO, YIELD and PNF of 0.97, 0.96, 0.96, -0.89, respectively). Carpelloid fruits exhibited a positive correlation with production traits, but negative correlation with physicochemical traits in papaya fruits. Moreover, there is a modest correlation between physicochemical and productive traits of Tainung no 1 and Local Variety fruits.
Keywords: Carica papaya L.; Genetic improvement; Variety performance